On the construction of super edge-magic total graphs - Darmaji Darmaji; Rinurwati Rinurwati; Suhud Wahyudi; Suhadi Wido Saputro (Electronic Journal of Graph Theory and Applications (EJGTA), 2022)
Suppose G = (V, E) be a simple graph with p vertices and q edges. An edge-magic total labeling of G is a bijection f : V ∪ E → {1, 2, …, p + q} where there exists a constant r for every edge xy in G such that f(x)+f(y)+f(xy)=r. An edge-magic total labeling f is called a super edge-magic total labeling if for every vertex v ∈ V(G), f(v)≤p. The super edge-magic total graph is a graph which admits a super edge-magic total labeling. In this paper, we consider some families of super edge-magic total graph G. We construct several graphs from G by adding some vertices and edges such that the new graphs are also super edge-magic total graphs.